Dividend Payout Ratio and Cost of Equity: A Case Study on the Industrial Sector of the Indonesia Stock Exchange - Christian Candra Wijaya; Sri Murni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The industrial sector plays a crucial role in driving Indonesia’s economic growth, yet it also faces challenges in optimizing capital structure and shareholder value. One key financial policy that reflects managerial decisions and investor perceptions is the dividend payout ratio, which may influence a firm’s cost of equity. This study aims to examine the effect of the dividend payout ratio on the cost of equity among industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research problem arises from inconsistent empirical evidence regarding whether higher dividend payments reduce or increase the cost of equity. Using a quantitative approach, secondary data were collected from annual financial reports, and samples were selected through purposive sampling, yielding 162 valid observations. Linear regression analysis was performed using EViews 13 software. The findings reveal a negative and statistically significant relationship between the dividend payout ratio and the cost of equity. The study concludes that higher dividend payouts can lower firms’ cost of equity, supporting the signaling theory.